Analisis Pengaruh Variasi Kecepatan Pengadukan pada Kualitas Hasil Cassava-Graphene Komposit - Ridho, Mukhlis Yazid; Ganda, Andita Nataria Fitri; Wulandari, Diah; Sakti, Arya Mahendra (Jurnal Rekayasa Mesin, 2023)
Starch as one of the basic ingredients for making plastic is easy to decompose, easy to process and its utilization will provide economic value because in Indonesia the availability of starch-based plants is quite abundant. This makes starch-based plants have a very big opportunity to be used as a material for making plastic. One of the plants made from starch is derived from cassava, both the contents and the skin. This research is intended to determine the process of composite materials that will be examined using the method that will be carried out with a focus on the analysis of composite materials from the influence of cassava graphene. The analysis is based on cassava peel starch mixed with graphene with a composition of 100 ml of mashed cassava peel starch and 15% graphene composition with a stirring variation of 500rpm and 700rpm. The results of the cassava graphene composite mixing process can determine the quality of the cassava- graphene results. The results obtained from the addition of graphene in a variation of 700rpm showed the results θ> 90°. From observations through the contact angle test method and water resistance test in the observation test sample. It can be concluded that variations in the addition of graphene in amounts above 15% make bioplastics have good properties that will be resistant to water.